2020
DOI: 10.22541/au.159413171.16884201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Recurrent Pulmonary Exacerbation in Idiopathic Pulmonary Hemosiderosis

Abstract: Objectives: To evaluate the risk factors of recurrent pulmonary exacerbation and poor prognosis in children with idiopathic pulmonary hemosiderosis (IPH). Methods: In this multicenter study, 54 patinets with diagnosis of IPH included. Medical records were retrospectively reviewed from three tertiary care hospitals between 1979 and 2019. Also, current information and the long-term progress of patients was determined by contacting the families by telephone. Results: A total of 54 children were included. The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…Surprisingly, we did not find any patients with autoantibodies other than those consistent with CD in our cohort. A recent study has shown a higher incidence of recurrence and worse outcomes in patients with ANA positivity 48 . Similarly, the presence of ANCA antibodies has also been associated with a poorer prognosis 64,65 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surprisingly, we did not find any patients with autoantibodies other than those consistent with CD in our cohort. A recent study has shown a higher incidence of recurrence and worse outcomes in patients with ANA positivity 48 . Similarly, the presence of ANCA antibodies has also been associated with a poorer prognosis 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective observational studies have reported the prevalence of celiac antibodies in pediatric patients with IPH. 11,42,48,49 The prevalence has varied between 17.6% and 40%. 50 Although only a small number of patients were tested and two of the studies 42,49 reported patients from the same French database, these studies suggest fairly high seropositivity for CD among patients with IPH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations